Feasibility of laparoscopy in management of ectopic pregnancy: experience from a tertiary care hospital - Meena, Jyoti; Vatsa, Richa; Kumar, Sunesh; Roy, Kallol K.; Yadav, Anshu; Singhal, Seema (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Ectopic pregnancy is an important cause of maternal morbidity and mortality. For surgical management, laparoscopy is preferred option. In developing world for ruptured ectopic pregnancy laparotomy is done at most of places. In this study we have assessed feasibility of laparoscopic management in both ruptured and unruptured ectopic pregnancy. Methods: A prospective study, conducted over period of 1 year from July 2014 to July 2015 in Department of Obstetrics & Gynecology, All India Institute of Medical Sciences, New Delhi. In 110 patients of ectopic pregnancy parameters studied were age and parity, symptoms, risk factors, diagnostic methods, site of ectopic, management and its outcome. Primary objective was to evaluate management outcome of ectopic pregnancy and to assess feasibility of laparoscopy in ectopic pregnancy. Ruptured ectopic pregnancy with massive hemoperitoneum were analyzed separately. Secondary objective was to study demographic characters and risk factors of ectopic pregnancy. Results: Surgical management was required in 93.6% patients, out of which 86.4% were managed laparoscopically. Unruptured ectopic pregnancy was managed successfully by laparoscopy in 96.6% (29/30) patients. Ectopic was ruptured in 73 (66.3%) cases, laparoscopy was attempted in 91.7% (67/73). In 10.4% (7/67) patients laparoscopy had to be converted to laparotomy and it was successful in 89.5%. Out of 16 patients with massive hemoperitoneum, 12(75%) were managed laparoscopically. There was no mortality. Conclusions: In most of cases laparoscopy is safe and successful. Laparoscopy is feasible in ruptured ectopic cases including selected cases with massive hemoperitoneum thus avoiding unnecessary laparotomy and associated morbidity. Timely diagnosis and management prevents mortality.